Immobilized molybdovanadophosphoric acids on SBA-15 for selective oxidation of alkenes - Raj, N. K. K.; Deshpande, S. S.; Ingle, Rohit H.; Raja, T.; Manikandan, Palanichamy (4th International Symposium on Nanoporous Materials, 2005)
Vanadium substituted molybdophosphoric acids have been immobilized on amine functionalized SBA-15 and characterized by different techniques. Small angle X-ray scattering analysis and SEM technique provide evidence for the structural integrity of the samples. UV-Vis, NMR and IR data confirm the incorporation of molybdovanadophosphoric acids onto the amine functionalized SBA-15. The textural properties of these materials were studied by nitrogen sorption studies. Oxidation of cyclooctene and norbornene was carried out with oxidants in aqueous (aq. H2O2) and non-aqueous (TBHP extracted in dichloroethane) medium. The reactions were carried out with both the neat catalysts (homogeneous) and the immobilized catalysts (heterogenized) and the results were compared. The selectivity of the desired products was always > 99% with the immobilized catalyst with both aq.H2O2 and TBHP. However, while the leaching was negligible in the non-aqueous medium, the aqueous medium leads to considerable leaching. The immobilized catalysts could be separated after the reaction and the reusability of the catalyst has also been demonstrated especially with oxidant in the nonaqueous medium.

Selective oxidation of ethane over Mo-V-Al-O oxide catalysts: insight to the factors affecting the selectivity of ethylene and acetic acid and structure-activity correlation studies - Sankaranarayanan, T. M.; Ingle, Rohit H.; Gaikwad, T. B.; Lokhande, S. K.; Raja, T.; Devi, R. N.; Ramaswamy, V.; Manikandan, Palanichamy (Catalysis Letters, 2008)
Catalysts of general formula, MoVAlOx were prepared with the initial elemental composition of 1:0.34:0.167 (Mo:V:Al) at a pH value in the range of 1-4. The elemental analysis showed that the final composition of the catalysts is pH dependant. The performance of the catalysts was tested for selective oxidation of ethane to give ethylene and acetic acid. While all of them were active for ethane oxidation with a moderate conversion, the catalyst prepared at pH 2 showed a highest activity with 23% ethane conversion and a combined selectivity of 80.6% to ethylene and acetic acid. The catalyst prepared at pH 4 was least selective to ethylene and acetic acid. Various techniques like powder XRD, SEM, Raman, UV-Vis and EPR were used to characterize the catalysts and to identify the active phases responsible for the selective oxidation of ethane. The powder XRD data showed that the catalysts prepared at pH 1 and 2 contain mainly of MoO3 and MoV2O8 along with traces of Mo4O11. The amount of MoO3 was slightly higher in the catalyst prepared at pH 1. However, the catalyst prepared at pH 3 contains mainly of MoV2O8 with no trace of MoO3. The catalyst prepared at pH 4 showed V2O5 as the major phase along with MoVAlO4 phase. The Raman data corroborated the XRD results. EPR and UV-Vis studies indicated the presence of traces of V-4 in pH 1 and 2 catalysts and significant amount of Mo5+ in all the catalysts. Thus, the high activity and selectivity to ethylene and acetic acid are attributed to the presence of MoV2O8 phase and other reduced species like Mo4O11 phase supported on MoO3. The presence of V and Mo ions in a partially reduced form seems to play a crucial role in the selective oxidation of ethane.
Keywords: Acetic acid; ethane; Ethylene; mixed metal oxide; Selective oxidation

Mixed metal oxide: a new class of catalyst for methanol activation - Mehta, Shweta; Agarwal, Sheena; Kenge, Nivedita; Mekala, Siva Prasad; Patil, Vipul; Raja, T.; Joshi, Kavita (Applied Surface Science, 2020)
In this work, we propose a mixed metal oxide as a catalyst and demonstrate it's ability to not only activate the MeOH molecule upon adsorption but also dissociate O-H and one of it's C-H bonds. MeOH activation is compared on two prominent facets of ZnAl(2)O(4 )viz. (2 2 0) and (31 1). While spontaneous O-H bond dissociation is observed on both facets, C-H bond dissociates only on the (3 1 1) surface. Multiple factors like atomic arrangement and steps on the surface, coordination of surface atoms, and their effective charges have a combined effect on MeOH activation. The (3 1 1) surface offers higher catalytic activity in comparison with (2 2 0) surface. Having a stepped surface, availability of multiple sites, and variation in the charge distribution are some of the reasons for better catalytic performance of (3 1 1) facet. Effect of orientation of MeOH with respect to the surface adds both, information and complexity to the problem. Observations pertinent to understanding this effect are also reported. A detailed analysis of atomic arrangement on the two surfaces provides a rationale as to why MeOH gets dissociated spontaneously on the mixed metal oxide. The promising results reported here opens up a new class of catalyst for research.
Keywords: DFT; MeOH; Spontaneous dissociation; ZnAl2O4

Unraveling the reaction mechanism of selective C9 monomeric phenols formation from lignin using Pd-Al2O3-activated biochar catalyst - Gurrala, L.; Kumar, M. M.; Yerrayya, Attada; Kandasamy, Prabu; Castano, Pedro; Raja, T.; Pilloni, Giovanni; Paek, C.; Vinu, R. (Bioresource Technology, 2022)
The conversion of biomass-derived lignin to valuable monomeric phenols at high selectivity is of paramount importance for sustainable biorefineries. In this study, a novel Pd-Al2O3 supported on activated biochar catalyst is developed for lignin hydrogenolysis. The catalyst characterization revealed that the (1 1 1) planes of both of Pd-0 and Al2O3 were exposed to the surface. The maximum lignin conversion of 70.4% along with high liquid yield (similar to 57 wt%) was obtained at 240 degrees C, 3 h and 3 MPa H-2 pressure. The total monomeric phenols yield in the liquid was 51.6 wt%, out of which C9 monomeric guaiacols constituted similar to 30.0 wt% with 38.0% selectivity to 4-propyl guaiacol. Using the reaction intermediate, coniferyl alcohol, chemoselective hydrogenation of C-alpha=C-beta is proved to occur over the Pd site, while dehydroxylation of C-gamma-OH is shown to occur over the alumina site. An impressive carbon atom economy of 60% was achieved for the production of monomeric phenols.
Keywords: Hydrogenolysis; lignin; Mechanism; Pd-Al/activated biochar; Propanol guaiacol; Propyl guaiacol